Analyzing the Applications and Implications of Current Emerging Technologies on Digital Trends - Genaro, Samuel; Rifiyanti, Hafizah (International Journal Education and Computer Studies (IJECS), 2023)
Advances in internet technology and social media have enabled direct and interactive consumer-business interactions via digital platforms. However, there is still a large gap in understanding the challenges and limitations that businesses face in effectively adopting this technology. This study aims to comprehensively explore the application of the latest technologies in digital marketing and offer actionable recommendations for optimizing their utilization in corporate marketing strategies. This research uses a literature-based approach for data collection and analysis. The rapid evolution of digital technology has greatly influenced the business landscape in Indonesia, with many digital platforms facilitating product promotion and sales. Although digital technology provides great benefits, it also presents various challenges and risks, especially in the field of digital marketing. This evolution underscores the efficacy of digital marketing as a powerful tool for product promotion. Leveraging social media and digital marketing strategies allows businesses to expand their reach to a wider target audience, attract potential customers and significantly increase sales figures. However, this has inherent challenges and risks, especially in maintaining data security and privacy, especially during online transactions and storing customer data. This research underscores the critical role of enforcing data security and privacy protocols to grow and maintain customer trust.